1971
DOI: 10.1113/jphysiol.1971.sp009587
|View full text |Cite
|
Sign up to set email alerts
|

Daily changes in amniotic and allantoic fluid during the last three months of pregnancy in conscious, unstressed ewes, with catheters in their foetal fluid sacs

Abstract: SUMMARY1. Catheters were inserted into the maternal and foetal vasculatures of ten ewes, 100-139 days pregnant, and daily samples ofuterine and umbilical blood and maternal jugular vein blood were taken for periods of 5-27 days after operation.2. Catheters were inserted into the fluid sacs of nineteen foetuses, 60-97 days post-conception, and daily samples were withdrawn for up to 90 days from amniotic sacs (eleven foetuses) and for up to 70 days from allantoic sacs (eight foetuses). Maternal jugular plasma wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
43
1

Year Published

1972
1972
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 40 publications
14
43
1
Order By: Relevance
“…The marked but temporary fall in the concentration of branched chain amino acids during the operative procedure was an expected response to the infusion of glucose and was probably due to the release of insulin, äs in other species (MUNRO [20]). The post-operative fall in blood urea of the control fetuses and that of the mothers in both groups confirm MELLOR and SLATER'S [18] observations in the ewe and those for the fetus, implied by the falling urea concentrations found in the allantoic fluid in the days following surgery. The results suggest an Inhibition of urea synthesis in both the mother and fetus following the hysterotomy; this is apparently in contrast to the findings of O'KEEFE et al [21] that moderate surgery reduces protein synthesis rate, but has little influence on protein bfeakdown.…”
Section: Discussionsupporting
confidence: 73%
“…The marked but temporary fall in the concentration of branched chain amino acids during the operative procedure was an expected response to the infusion of glucose and was probably due to the release of insulin, äs in other species (MUNRO [20]). The post-operative fall in blood urea of the control fetuses and that of the mothers in both groups confirm MELLOR and SLATER'S [18] observations in the ewe and those for the fetus, implied by the falling urea concentrations found in the allantoic fluid in the days following surgery. The results suggest an Inhibition of urea synthesis in both the mother and fetus following the hysterotomy; this is apparently in contrast to the findings of O'KEEFE et al [21] that moderate surgery reduces protein synthesis rate, but has little influence on protein bfeakdown.…”
Section: Discussionsupporting
confidence: 73%
“…Such patterns would be consistent with the suggestion that fetal urine is a source of agalactosidase and /Y-acetyl-ß-hexosaminidase activities and that sheep fetal urine is first accumulated in the allantoic sac via the urachus up to a gestational age of 86-90 days and thereafter passes more and more into the amniotic sac. This is thought to be due to the occlusion of the urachus and increasing potency of the urethra (Smith et al, 1966;Mellor & Slater, 1971. The protein concentration also followed a similar pattern being about 6-fold more elevated in allantoic than in amniotic fluid at 49-65 days and reaching approximately equal concentrations in both sacs at 106-132 days.…”
Section: Discussionmentioning
confidence: 49%
“…Evidence has been found that the human fetus releases its intestinal content into the amniotic cavity: Benzie & Doran (1975), using a special endoscope, observed fetal defaecation in utero in an 18-week fetus, and the presence of intestinal disaccharidases (Potier et al, 1975(Potier et al, , 1976 and biliary salts (Délèze, Sidiropoulos & Paumgartner, 1977) has been reported in amniotic fluid. The pregnant ewe is particularly useful for study of the origin of amniotic fluid enzymes because the fetal urine is apparently accumulated in the allantoic cavity early in gestation (Smith, Adams, Borden & Hilburn, 1966;Mellor & Slater, 1971 while intestinal enzymes are extruded in the amniotic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…There are also progressive changes in amniotic fluid composition over gestation (Mellor & Slater, 1971 Jacobson (1970) has suggested that whereas the connexions of some neurones are genetically established, the specific connexions of others are dependent on sensory stimulation during early development. The taste experiences of the foetus may, then, determine the taste sensitivities and preferences of the adult.…”
Section: Discussionmentioning
confidence: 99%